Dravet Syndrome: A case report - Akter, Aireen; Alam , Syeda Tabassum; Ahmed, Sanjida (Journal of Bangladesh College of Physicians and Surgeons, 2026)
Dravet syndrome is a rare genetic epileptic encephalopathy characterized by drug resistant epilepsy. Patients present with prolong febrile seizure with normal developmental status in infancy. However patient may experience a halt or decline of development usually after one year of age. This type of presentation may mimic other neurological disorder like simple febrile seizure, mitochondrial disorder and other epileptic encephalopathies. Though clinical presentations almost similar, confirmation require genetic evaluation for counseling and management purpose. We recently observed a two-year-old boy with Dravet syndrome confirmed by identifying mutation of SCN1A gene. MRI of brain revealed moderate cerebral atrophy and enlarged brain ventricles. J Bangladesh Coll Phys Surg 2026; 44: 64-67